PROSPEK PEMBANGUNAN SUB TERMINAL AGRIBISNIS DALAM RANGKA PERBAIKAN KINERJA PEMASARAN DAN PENINGKATAN PENDAPATAN PETANI DI WILAYAH TIMUR KABUPATEN SIKKA - Noni, Sarlina; Darmawan, Dwi Putra; Suarthana, Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 3 No 1 (2015): Vol. 3 - No. 1 - Mei 2015, 2015)
Sub-terminal agribusiness, marketing agencies or concept as a market that is well managed to increase added value to farmers, in addition to educating farmers improve the quality of its products, as well as change the mindset toward agribusiness and became one of the original sources of income of the region. This research aims to study the development of agribusiness sub-terminal, the factors that affect the role of man, money, machines, methods, market in the construction of sub terminal agribusiness and agribusiness development influence sub terminal of performance marketing and an increase in revenue. This research was conducted in the eastern region of sikka on seven districts (Kewapante, Hewokloang, Bola, Doreng, Waigete, Talibura, Waiblama), which is the producer of crop plantations. Determination of the number of respondents is based on the number of respondents with slovin methods as much as 98 people, retrieval technique using purposif method of sampling respondents. Data collection techniques include: observation, interviews, and documentation, and data analysis using the method of quantitative analysis with test PLS. The results showed that the role of the factor man, money, machines, methods, market development of sub terminal agribusiness is very high, with the highest factor is the role of money and the correlation between a factor and mutually binding is the highest factor method. Construction of the sub-terminal agribusiness is real and positive affect performance marketing, the biggest factor is the factor of influence machines and produc. Construction of the sub-terminal agribusiness is real and positive influence of income with respect to the measurement of each factor is a positive and very real. Machines and creativity factor is the factor that has the most influence is high. Influence directly the sub terminal of agribusiness marketing and income is very real, as are the direct influence of marketing revenue. The suggestions can be put forward: (1) the role of government and private institutions as well as in the repair of chain or a marketing system as long as it does not favour to farmers producing crops of farmer plantations mainly by improving the existing marketing systems and monitoring of market prices, (2) a binding between the joint government and private institutions in strengthening marketing, repair and construction of infra structure: roads, bridges, ports, storage sheds to grow smooth results marketing process, (3) need for cooperation by all parties both from the educational institutions/universities, governments and private institutions to assist farmers in improving usahataninya, and (4) sikka to government as soon as possible to build a sub terminal agribusiness which is one of the marketing agency that coordinated or arranged properly to improve marketing systems that have an impact on increased life and well-being of farmers ' lives.
Keywords: development, sub terminal agribusiness, marketing performance, and increased opinion